The effect of NaOH concentration and stem size in the making of Oxalic Acid from Banana Stem - Didik Purwanto; A Rasmito; Sihabuddin Sihabuddin (Journal of Applied Sciences, Management and Engineering Technology, 2022)
The main purpose of this research is to determine the effect of NaOH concentration and size of banana stem pieces on the concentration of oxalic acid produced. The experiment procedure is add 20 grams of banana stems that have been dried into 200 ml NaOH then heated and stirred at temperature of 100°C for 1 hour. Then the molten mixture was added with hot 500 ml of water, then cooled and filtered. Filtrate was taken and added to 100 ml CaCl2. Solution is filtered and the sediment is taken. Sediment is inserted into the Erlenmeyer and 200 ml dilute H2SO4 added and then filtered. 10 g active carbon is added into filtrate of the solution, then filtered. Taking 10 ml of the filtrate above to be titrated. From the research has been done, it can be concluded that the greater the concentration of NaOH, the greater the amount of oxalic acid obtained. The longer the size of the banana midrib, the greater the amount of oxalic acid obtained. And, the maximum amount of oxalic acid obtained is 2.99 g that reach at a concentration of 50% NaOH with a length of the banana leaf 2.5 cm.